The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31020/mutftd.693100
|View full text |Cite
|
Sign up to set email alerts
|

Yoğun Bakım Hemşirelerinin Ötanazi, Ölüm ve Ölümcül Hastaya Karşı Tutumları

Abstract: Giriş: Hemşireler hastane ortamında yaşanılan ölümlere en yakın tanıklık eden sağlık profesyonellerindendir. Özellikle yoğun bakım hemşireleri bu durumla daha çok karşı karşıya kalmaktadırlar. Amaç: Bu çalışmanın amacı da üniversite hastanesinin yoğun bakım ünitesinde görev alan hemşirelerin ötanazi, ölüm, ölümcül hastaya yaklaşım konusundaki tutumlarını belirlemektir. Gereç ve Yöntem:Araştırmanın veri toplama formu iki kısımdan oluşmaktadır. Birinci kısımda 16 soruluk kişisel bilgi formu; ikinci kısımda Ötana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In studies that focused on the attitudes of students who intend to become health care workers towards mental health conditions, it was seen that students accept depression as a disease and have a positive perspective towards the phenomenon of depression, such as the study conducted on pharmacy students in Saudi Arabia [38]. However, in other studies, students reported negative attitudes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In studies that focused on the attitudes of students who intend to become health care workers towards mental health conditions, it was seen that students accept depression as a disease and have a positive perspective towards the phenomenon of depression, such as the study conducted on pharmacy students in Saudi Arabia [38]. However, in other studies, students reported negative attitudes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Participants with incomplete information or who did not agree to participate in the study were excluded from the study. A questionnaire consisting of demographic data such as gender, age, tenure, education, titles, information on euthanasia, and Attitudes towards Euthanasia, Death, and the Terminally Patient (EDTP) was distributed to the participants [10]. The questionnaires that were withdrawn from the participants and that met the inclusion criteria were analyzed by hiding the identity of the participants.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of 31 questions answered with a 4-point Likert scale. Questions 3,6,7,8,10,12,13,15,16,17,20,23,24,27 in the scale are reverse scored. The 5-factor analysis specified in the study published by Şenol et al in 1996 was carried out [11].…”
Section: Edtp Scale Applicationmentioning
confidence: 99%
“…caring for patients (Ciechaniewicz et al, 2010). Boerner et al (2017) reported that emotions associated with the death of the patient play an important role in occupational burnout in long-term care workers (Boerner et al, 2017).…”
Section: J N C Rmentioning
confidence: 99%
“…The Nurse Information Form, End-of-Life Care Attitudes and Behaviors Scale (EACAS) of Intensive Care Nurses, and Psychological Well-Being Scale (PWBS) were used to collect the data. The Nurse Information Form was created by the researchers in line with the literature to obtain sociodemographic information about nurses (Can et al, 2020;Erzincanlı & Kasar, 2022;Keskin-Kızıltepe & Kurtgöz, 2022;Özel-Yalçınkaya, 2016;Selvi, 2019). This form includes questions about the participants' age, gender, marital status, education level, unit of employment, years of employment, and their thoughts on death and end-of-life care.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%